Aprendizagens ancestrais desenhadas por corpos-territórios de crianças em casas de candomblé da Nação Angola Muxicongo - Conceição , Ailma (Muzakiri) da Silva (2023)
This work proposes to analyze the visual graphic elements drawn by bodies- territories of children with Afro-Brazilian identities who live in the spaces of a Candomblé terreiro of the Angola Muxicongo Nation, located in the city of Salvador, Bahia. To this end, I intend to answer the following problem: how do bodies- territories of children from the Angola Muxicongo nation pass on learning Ancestors ritualized in their drawing productions? I present as objective general understanding of how the bodies-territories of terreiro children reflect the Ancestral learning ritualized in their drawing productions. As objectives specific, I present: mapping the history of Children's Drawing and its correlation with Education in Terreiros; investigate through the drawings of children from the nation of Angola Muxicongo the presence of ancestral knowledge projected into their bodies-territories; identify the importance of the Afro-Brazilian contribution to the construction of values civilizations present in children’s drawings. When working with the phenomenon of research, which are the children who are part of the Candomblé terreiro spaces, It is important to understand how these places have a rich ancestral legacy that builds the cultural identity of these children and highlights values identity of belonging and appropriation of the history of our people. This ancestral legacy It is constituted through myths, symbols and orality. The design discussed in this work seeks to understand how the bodies-territories of these children constitute their identities and externalize them through images that are traced and scribbled in pencil, paper and photography. At this juncture, the categories Children's Drawing, Education in Terreiros, Decolonial Education, Body-Territory, and African Legacy, associated with the methodology of sociopoetics. To this end, the methodological basis allows us to direct coexistence in study spaces, valuing the imagination and bodies of these children as producers of knowledge. In this way, it allows workshops to understand how children, through their eyes, trace their stories cultural and symbolic representations existing in the spaces of a terreiro de Candomblé.